Preparation of Fe3Si‐Al2O3 Nanocomposite Powders by Mechanochemical Reaction of Fe3O4‐Si‐Al Powder Mixtures. Issue 6 (22nd February 2013) - Jia, Jiangang; Guo, Tieming; Ren, Shufang; Lu, Jinjun; Ma, Qin
<x xml:space="preserve">Abstract</x> Phase evolution and morphology of Fe3O4‐Si‐Al powder mixtures during ball milling from 30 min to 20 h were investigated. A 3‐h critical milling was necessary for the occurrence of mechanically activated combustion reaction. The reaction results in the formation of Fe (Si), Fe3Si, and α‐Al2O3. During ball milling from 3 to 20 h, Fe (Si) and Fe3Si were combined into disordered Fe3Si intermetallic and Fe3Si‐Al2O3 composite powder was formed. The presence of in situ formed alumina leads to a decrease in crystallite and particle sizes. The Fe3Si‐Al2O3 particles after milling for 20 h had a crystalline size of 10~12 nm.